Study Quality Microbiology of Catfish (Hemibagrus nemurus) Cage Cultivation in Kampar River, Riau - Reinaldy Pangestu; Bustari Hasan; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractCatfish is a type of freshwater catfish that lives in river waters. The information about on the microbial existence, inculding the Total Plate Count (TPC) of microbia, Coliform, Escherichia coli, and Salmonella sp. in the fish cultivated in a cage in the River in Kampar have not discovered yet. This research was aimed to evaluate the microbiological quality of catfish cultivated in cages in the River of Kampar, Riau. The results showed that the microbiology quality of the fish, collected from 3 different sampling stations, have been evaluated that the samples collected from fish-cages in Air Tiris (K1) station, the number of total bacteria (TPC) counted was 4.4 x 103 Cfu/g, the number of Coliform bacteria was8.87 MPN/g, the number of Escherichia coli bacteria was negative, the number of Salmonella sp. Was negative. The samples collected from fish-cage in Teratak (K2) station was counted that the number of total bacteria (TPC) was 3.3 x 103 Cfu/g, the number of Coliform bacteria was6.87 MPN/g, the number ofEscherichia coli bacterial was negative, and the number of Salmonella sp. was negative. The samples collected from fish-cage in Buluh (K3) station was counted that the number of total bacteria (TPC) was 4.3 x 103 Cfu/g, the number of Coliform bacteria was 7.93 MPN/g, the number of Escherichia coli bacteria was negative, and the number of Salmonella sp. was also negative. It can be concluded that the highest microbiological quality was found in cage-cultivatesd catfish in Teratak Buluh. Keywords: bacteria, coliform, hemibagrus, total plate count